Enthusiastic portrayal of 3D bioprinting in the media: Ethical side effects. (24th November 2017) - Gilbert, Frederic; Viaña, John Noel M.; O'Connell, Cathal D.; Dodds, Susan
Abstract: There has been a surge in mass media reports extolling the potential for using three‐dimensional printing of biomaterials (3D bioprinting) to treat a wide range of clinical conditions. Given that mass media is recognized as one of the most important sources of health and medical information for the general public, especially prospective patients, we report and discuss the ethical consequences of coverage of 3D bioprinting in the media. First, we illustrate how positive mass media narratives of a similar biofabricated technology, namely the Macchiarini scaffold tracheas, which was involved in lethal experimental human trials, influenced potential patient perceptions. Second, we report and analyze the positively biased and enthusiastic portrayal of 3D bioprinting in mass media. Third, we examine the lack of regulation and absence of discussion about risks associated with bioprinting technology. Fourth, we explore how media misunderstanding is dangerously misleading the narrative about the technology.